2018
DOI: 10.1016/j.cpr.2017.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in bipolar disorders: Implications for emotion

Abstract: Prominent cognitive deficits have been documented in bipolar disorder, and multiple studies suggest that these deficits can be observed among non-affected first-degree relatives of those with bipolar disorder. Although there is variability in the degree of cognitive deficits, these deficits are robustly relevant for functional outcomes. A separate literature documents clear difficulties in emotionality, emotion regulation, and emotion-relevant impulsivity within bipolar disorder, and demonstrates that these em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
93
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 151 publications
8
93
1
1
Order By: Relevance
“…41,42 While the latter is particularly associated with successful emotional regulation, social skills may independently impact clinical outcome, suggesting that the neurological effect of disease burden in bipolar disorder may impair long-term functionality through multiple mechanisms. 43,44 In contrast to our initial hypothesis, the relatively lower prefrontal activation observed in multi-episode bipolar subjects was not associated with greater amygdala activation. Instead, we found lower amygdala activity in multi-episode subjects.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…41,42 While the latter is particularly associated with successful emotional regulation, social skills may independently impact clinical outcome, suggesting that the neurological effect of disease burden in bipolar disorder may impair long-term functionality through multiple mechanisms. 43,44 In contrast to our initial hypothesis, the relatively lower prefrontal activation observed in multi-episode bipolar subjects was not associated with greater amygdala activation. Instead, we found lower amygdala activity in multi-episode subjects.…”
Section: Discussioncontrasting
confidence: 91%
“…35 These findings are consistent with previous observations of functional differences across posterior parietal regions of bipolar patients; and with observations of executive dysfunction and functional decline associated with bipolar progression. While the latter is particularly associated with successful emotional regulation, social skills may independently impact clinical outcome, suggesting that the neurological effect of disease burden in bipolar disorder may impair long-term functionality through multiple mechanisms 43,44. Activity in Brodmann area 22 may have been mobilized by the social cognition aspects of viewing negative anthropinistic pictures, and decrements in activation of this region are consistent with observations of impaired social cognition and verbal fluency in many individuals with bipolar disorder 41,42.…”
supporting
confidence: 71%
“…The bifurcation of cognitive profiles was the most striking finding with respect to diagnoses: compared to healthy controls, SCZ and BP-I showed pronounced deficits across executive function, social cognition and motor speed tests relative to memory and complex cognition, while BP-II and MDD displayed mild cognitive impairment, across domains, with intact nonverbal reasoning. This result aligns with a growing body of evidence indicating heterogeneity of neurocognitive function within BPD (27), and provides a possible explanation for a similarly bifurcated pattern of genetic correlations between the SMI diagnoses revealed in recent large-scale GWAS datasets (28). The large trans-diagnostic sample also enabled us to identify a significant interaction between test domain, diagnosis and sex, as females with SCZ, BP-I, and MDD were slower than males in measures of executive speed.…”
Section: Discussionsupporting
confidence: 81%
“…Zhou et al () conducted a study on PM deficits in euthymic bipolar disorder patients and found that patients performed poorly on both TB and EB PM. The current findings, therefore, can be attributed to the fact that cognitive impairments are common in bipolar disorder (Lima, Peckham, & Johnson, ; Martínez‐Arán et al, ; Robinson et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Absolute mood stability is unusual in bipolar disorder, and subclinical depressive symptoms are commonly seen in such populations (Goodwin, Martinez‐Aran, Glahn, & Vieta, ), which were also found in the participants of this study during the clinical interview. Research states that there is the potential for an effect of prevailing affective state to reduce cognitive functions (Patterson et al, ; Lima et al, ) and so it can be assumed that such symptomatology of the participants has resulted in a deficit in prospective remembering in the study. Moreover, most of the participants of the present study had a chronic course, which can also be an attributing factor to worsened cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%